(untitled) (Eurasian Journal of Philology Science and Education, 2015)
Bolshevik revolution existence matters of the movement and development of the revolution were the main subject of the new Azerbaijan novels of 1930-50 years. In fact, the main heroes of those works of literature were the revolutionaries. In the article, the regard is expressed to the revolution and revolutionary conceptions from the point of new social-literary thought, political-literary features of the very novels written in the level of concrete demands of the socialist realism method is stated